PENGARUH BIMBINGAN SPIRITUAL TERHADAP TINGKAT KECEMASAN KLIEN PREOPERASI LAPARATOMI DI INSTALASI BEDAH SENTRAL - Topan Iman Sanjaya; Lidia Hastuti; Tri Wahyuni (Jurnal Keperawatan dan Kesehatan, 2022)
Background: Anxiety is a feeling of uncertainty and helplessness that afflicts almost everyone at some point in their life. in clients who will undergo surgery, often experience anxiety. Clients who will undergo surgery can only sleep approximately 4-6 hours/day due to anxiety and pain and others, including shortness of breath, sweating, flatulence, hot or cold air and discomfort. The client experiences anxiety before undergoing surgery, one of which is laparotomy surgery. Objective: To determine the effect of spiritual guidance on the anxiety level of pre-laparotomy clients at the central surgical installation of RSUD Dokter Soedarso Pontianak. Methods: This study used a quasi-experimental pretest-posttest design with two group design, random sampling technique, the number of respondents was 32 people divided into treatment and kontrol groups. Samples were taken from the population of preoperative laparotomy clients in the central surgical installation room at RSUD Dokter Soedarso who met the inclusion criteria. Collecting data using a questionnaire. Data were analyzed using the wilcoxon rank tests. Results: The study showed that there was a significant relationship between spiritual guidance (praying, tawakal and motivation) with a decrease in anxiety levels of pre-laparotomy clients at the central surgical installation of RSUD Dokter Soedarso Pontianak with a value of =0.008 (p<0.05). Conclusion: Spiritual guidance in the form of prayer and tawakal has an effect on the level of anxiety in laparotomy clients who will undergo surgery so that the risk of delaying surgery can be reduced. Keywords: spiritual guidance, anxiety, preoperative laparatomy.